Religious and Health Benefits of Salah/Prayer: A Review - Yusuf Sarkingobir; Aliyu Umar Sharu; Mustapha Sahabi; Nafisa Abdulrahman Ashafa (International Journal of Emerging Issues in Islamic Studies, 2022)
Religion is very influential in health promotion. One of the major components of the Islamic religion is Salah/prayer, performed by the majority of Muslims five times daily. Thus, there is a need to broach the religious and health benefits of prayer. A review of related literature was performed, and the results were obtained. It was observed that prayer has several religious and health benefits to the adherents and hence can serve as a health promotion tool. Religiously, performing prayer is the fulfillment of a major pillar of Islam and Allah's commandment. From a health point of view, performing Salah is a very important exercise that is severally beneficial to health. It improves physical and spiritual domains of health. Mental health is also improved because of Salah. Particularly, improvement in heart, spine, memory, concentration, cognitive functions, rehabilitation of musculoskeletal and neurological conditions, maintenance of joint mobility and elasticity, acting as endurance exercise, reduction in cardiovascular problems, and increase in mental health are some selected health advantages of prayer. Before prayer, there is ablution that involves some etiquettes as follows: trimming of the moustache, the use of siwak (tooth- stick), cleaning of the nose, clipping of fingernails, washing of knuckles, removing hair from armpits and pubic area, cleaning the genitals, one should not urinate while standing because it can splash and affect his body, clothes or relations, one should clean himself from impurities, one should not use the right hand in cleaning dirt, one should wash his hands with water, then soap after toilet. Prayer is indeed beneficial to the health of performers.